Study on Factors Affecting The Successful Implementation of Construction Projects in West Lombok District and Mataram City - Sayfuddin Sayfuddin (Journal of Applied Engineering and Technological Science (JAETS), 2022)
A construction project that can be completed properly is the result of a combination and interaction of various related activities, elements and processes, both planned and unplanned and in a changing environment, several factors are more dominant in influencing project success. to help allocate available resources. The purpose of this research is to find out the factors for the success of a construction project and the extent of the influence of these factors on the success of the project, especially the implementation of construction in the district of West Lombok and the city of Mataram. The ultimate goal of this research is to provide tools for parties involved in the implementation of construction, to predict project success and provide useful information in allocating resources to produce satisfactory results. This research consists of two stages, namely the pilot study and the second stage of research. In the pilot study in the form of a questionnaire containing questions referring to Chan's research (1998), it has succeeded in obtaining data from 60 respondents from business practitioners in the construction service sector in the district of West Lombok. Mataram city. The second phase of the questionnaire obtained data for 52 respondents consisting of project owners, professional practitioners, both consultants and contractors. The mean value of the tap factors from a total of 44 variables resulted in the 15 factors with the highest ranking. The fifteen factors were analyzed by step wise multiple regression to determine the extent of the influence of each factor on the project's success criteria. The six most dominant factors influencing project success are the project owner's emphasis on time, quality and cost of supervision, involvement with the implementation team from the start, health & safety programs supported by the parent company, and relationships with fellow business associates.The results of the study prove that the project design factors that are adequate enough to be carried out at the construction implementation stage are the factors that most influence the project's success, followed by supervision at the construction implementation stage running well, the project team's technical ability, communication between the parties involved in the implementation. construction, and regular coordination.